AN ANALYSIS OF EXTERNAL CONFLICT IN BIG HERO 6 MOVIE - Gede Ardynata Dewa (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
Abstract— The aims of this study are to analyze types of conflict and conflict management strategy that faced by the characters in the movie Big Hero 6. The data source of this research was the movie Big Hero 6 which was published in 2014 and directed by Don Hall and Chris William. The data was collected through documentation method, by watching the movie repeatedly, and then the data was identified and selected the data that was used in this research. The collected data was analyzed qualitatively and presented descriptively. A theory that was used in this research was proposed by Kenney (1966:19) about types of conflict and how the main character resolved the conflicts proposed by Deetz and Stevenson in Fleetwood (1987). Based on the research, it shows that all types of conflict that faced by the characters and how the main characters resolve the conflicts in Big Hero 6 Movie. There are external conflict, and conflict management strategy that was compromise and competition.